Synergy of Losartan and chemotherapy for patients with cholangiocarcinoma: A propensity score-matched analysis - Li, Qing; Chang, Zhenyu; Wang, Tianyi; Liu, Bing; Wang, Ximin; Ge, Xin-Yu; Yang, Tao; Liu, Qu; Wang, Wei (Frontiers in Oncology, 2022)
Background Cholangiocarcinoma (CCA) is a malignant tumor originating from bile duct epithelial cells that no obvious clinical symptoms and specific clinical manifestations are shown in the early stage of CCA Methods Propensity score matching (PSM) is a quasi-experimental method in which this study used. Patients were enrolled from Department of General surgery, First Affiliated Hospital of Jinzhou Medical University from March 1, 2010, to December 30, 2019. Totally 170 patients with CCA were enrolled in this study. Results We performed a 1:2 PSM study and found that patients with losartan group showed both comparable median OS (overall survival) and TTR (time to recurrence) to those in the patients without losartan group before PSM. However, after matching, patients with losartan group showed favorable median OS and TTR than those in the patients without losartan group. Then we performed Cox proportional hazards models and found that patients with losartan was an independent factor after multivariable analysis for patients with CCA. Furtherly, we sequenced serial cfDNA were performed in 10 patients with losartan and 9 patients without losartan who received adjuvant chemotherapy after tumor resection. These results showed that the treatment of losartan was related with tumor microenvironment and could be potentially useful to combine the immunotherapy for patients with CCA. Conclusion In conclusion, this study demonstrated that the treatment of losartan could increase the efficacy of adjuvant chemotherapy and identified as an independent survival predictor for patients with CCA. Moreover, losartan could be potentially useful to combine the immunotherapy for patients with CCA.